Pertanggungjawaban Hukum Dokter Lulusan Luar Negeri dalam Pelayanan Kesehatan di Indonesia: Legal Responsibility of Foreign-Trained Doctors in Health Services in Indonesia - Rahmatullah, Dyko; Sutarno; Nugraheni, Ninis (Jurnal Hukum dan Etika Kesehatan, 2026)
The shortage of medical personnel in Indonesia is influenced by the uneven distribution of doctors in remote areas, limited medical education capacity, and relatively lengthy licensing bureaucracy. These conditions have led to the utilization of Indonesian citizens who graduated from foreign universities (WNI-LLN) as an alternative to fulfill health services. This study aims to analyze the regulations on equivalence and legal accountability of WNI-LLN doctors in health services in Indonesia. The method used is normative juridical research with a legislative, conceptual, comparative, and case approach. The results of the study show that regulations regarding the equivalence of diplomas, competency tests, adaptation programs, and the issuance of Registration Certificates (STR) and Practice Licenses (SIP) are regulated in Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024. However, its implementation still faces administrative obstacles and suboptimal supervision. Therefore, it is necessary to strengthen the verification system, digitize STR–SIP services, and improve supervision and legal education for the profession to ensure patient protection and legal certainty for medical personnel.